2021
DOI: 10.1182/bloodadvances.2021004698
|View full text |Cite
|
Sign up to set email alerts
|

Risk of pulmonary emboli after removal of an upper extremity central catheter associated with a deep vein thrombosis

Abstract: Standard treatment of catheter-associated upper extremity deep vein thrombosis (UE-DVT) is anticoagulation, although catheters are often removed for this indication. The optimal time for catheter removal and whether the act and/or timing of catheter removal is associated with pulmonary embolism (PE) remain unknown. A retrospective cohort study was performed at 8 participating institutions through the Venous thromboEmbolism Network US. Patients with hematologic malignancies and central venous catheter (CVC)–ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“… 13 However, these recommendations to overlap therapeutic anticoagulation with catheter removal are not based on strong evidence, and the variation in recommended days can be confusing for clinicians, thus leading to the lack of uniformity in treatment approaches. Anticoagulation for several days before removal is intended to minimize the risk of embolization; however, a recent study by Houghton et al 37 showed that early catheter removal (<48 hours after anticoagulant initiation) in patients with hematologic malignancies and CRT was not associated with increased risk of pulmonary embolism within 7 days. This finding aligns with our study, as none of the patients developed PE within 7 days from presentation.…”
Section: Discussionmentioning
confidence: 99%
“… 13 However, these recommendations to overlap therapeutic anticoagulation with catheter removal are not based on strong evidence, and the variation in recommended days can be confusing for clinicians, thus leading to the lack of uniformity in treatment approaches. Anticoagulation for several days before removal is intended to minimize the risk of embolization; however, a recent study by Houghton et al 37 showed that early catheter removal (<48 hours after anticoagulant initiation) in patients with hematologic malignancies and CRT was not associated with increased risk of pulmonary embolism within 7 days. This finding aligns with our study, as none of the patients developed PE within 7 days from presentation.…”
Section: Discussionmentioning
confidence: 99%
“…This grouping was independent from subjects’ use of prophylactic anticoagulation. Forty‐eight hours was chosen as a timeframe that had previously been established (through the VENUS study) 9 as a timing of concern for early removal of CVCs.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study by Houghton et al by the Venous Thromboembolism Network United States (VENUS) evaluated this clinical scenario in adult cancer patients with upper extremity CRT. 9 In their cohort of 663 subjects, there was no difference in rates of embolization with less than or greater than 48 h of anticoagulation prior to CVC removal. To address this issue in children, this current study evaluated the incidence of symptomatic pulmonary embolism (PE) after CVC removal in children within the multi-institutional Children's Hospital-Acquired Thrombosis (CHAT) Consortium Registry diagnosed with a CRT.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“… 110 However, a recent study of 626 patients with acute CRT showed that early (≤48 h) removal of CVCs (with and without anticoagulation) was not associated with an increased risk of PE within 7 days compared with delayed (>48 h) or no removal (0.78% versus 0.44%; respectively, P > 0.9). 112 All 3 patients with PE had brachiocephalic vein or superior vena cava thrombosis as the index CRT. Therefore, in patients with brachiocephalic vein or superior vena cava thrombosis, the benefit of early removal should be carefully weighed against a potential thromboembolic risk.…”
Section: Anticoagulant Therapymentioning
confidence: 99%